Dampak Pandemi Covid 19 terhadap Perubahan Harga Saham dan Volume Transaksi pada PT. Ramayana Lestari Sentosa, TBK - Cyntia Carolina (Journal on Education, 2022)
This study aims to determine whether there are significant differences in stock prices and transaction volume due to Covid 19 (Case study at PT.Ramayana Lestari Sentosa Tbk). The data for this study were taken two years before the announcement of the first case of covid 19 in Indonesia, namely the period March 2018 - February 2020 and two years after the announcement of the first case of covid 19 in Indonesia, namely the period March 2020 - February 2022. The data was processed using a paired sample t-test. The results of this study indicate that there is a significant difference between the stock prices two years before and two years after the announcement of the first case of Covid 19 in Indonesia.